The Mode 3 Networked University: A New Materialist Perspective - Matthews, Adam (Proceedings of the International Conference on Networked Learning, 2024)
The idea of a modern university is a constantly changing and often contested concept. This paper traces the idea of a university using three modes. These modes are the Mode 1 Ivory Tower, Mode 2 Factory and Mode 3 Network. This framework draws upon higher education literature as well as three modes of knowledge production. I use these modes as a framework to describe the genealogical and historical development of the university in the Western world. These however are not purely historical and elements of their characteristics can be found within and between university institutions today. A genealogy shows a historical path dependency (i.e a teaching and research institution) of the idea of a university and a new materialism perspective shows the coming together of the many elements of the network assemblage which includes the discourse on the idea of a university clashing with new ideas, technologies and policy. The growth and development of the modern university from small, autonomous, elite and autonomous in mode 1 to large, mass regulated factory with marketplace outputs within neoliberal societies is well documented. The Mode 3 Network University is emerging with a potential for universal access with networked societies and technologies and has many actors influencing its becoming and idea. The 2020 Covid-19 pandemic and a broadening multidisciplinary approach to the field of Networked Learning has been called for and I introduce the possibility of theoretically analysing the becoming and enactment of the Mode 3 Network University using concepts and frameworks from the broad field of New Materialism. Such approaches take into account the complex assemblage and network of actors which are human and non-human in the growing and diversifying university. The growth and marketisation of the university has added to this complexity with commercial ’unbundling’ taking place. Degrees, institutions and functions are being unbundled and rebundled and this active complex network of actors including technologies, humans (academics, students, employers, wider public) and the residual path dependency of the three modes are in tension and conflict but come together to enact the modern university. New Material methodologies allow for these many influences to come together in a ’flat ontology’ to allow for a more nuanced and new approach to research in Networked Learning.